Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kineja Pegawai di Dinas Penanaman Modal dan Pelayanan Perizinan Terpadu Satu Pintu (DPMPPTSP) Kabupaten Tapanuli Tengah - Pasaribu, Theressa Taken (Universitas Batanghari Jambi, 2025)
This study aims to determine the influence of leadership style and organizational culture on employee performance at the DPMPPTSP of Central Tapanuli Regency. This study is a saturated sampling, meaning that all 60 State Civil Apparatus (SCA) at DPMPPTSP are sampled. This study also uses a quantitative approach with data collection techniques through questionnaires distributed directly to respondents, then analyzed using multiple linear regression analysis. The results of this study indicate that simultaneously and partially there is a positive and significant influence between the variables of leadership style and organizational culture on employee performance at the DPMPPTSP of Central Tapanuli Regency